2019
DOI: 10.1007/978-3-030-11726-9_17
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Segmentation with Cascaded UNet

Abstract: 2[0000−0002−2880−2887] , Evgeny Vasiliev 1[0000−0002−7949−1919] , and Vadim Turlapov 1[0000−0001−8484−0565]Abstract. MRI analysis takes central position in brain tumor diagnosis and treatment, thus it's precise evaluation is crucially important. However, it's 3D nature imposes several challenges, so the analysis is often performed on 2D projections that reduces the complexity, but increases bias. On the other hand, time consuming 3D evaluation, like, segmentation, is able to provide precise estimation of a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 10 publications
(18 reference statements)
0
28
0
Order By: Relevance
“…We compare three models: UNET, HEDNet and HED-Net with cGAN. UNET, which was originally proposed for biomedical image segmentation [8], is a standard and widely used model [9,11,10]. Results show that our HEDNet+cGAN model improves over both HEDNet and UNET.…”
Section: Quantitative Resultsmentioning
confidence: 96%
“…We compare three models: UNET, HEDNet and HED-Net with cGAN. UNET, which was originally proposed for biomedical image segmentation [8], is a standard and widely used model [9,11,10]. Results show that our HEDNet+cGAN model improves over both HEDNet and UNET.…”
Section: Quantitative Resultsmentioning
confidence: 96%
“…These algorithms can be trained directly on the 3D volume. Among the solutions, it is worth considering the results presented in Reference [81] in which the authors have trained a U-net network on images from BRATS 2018 and they have demonstrated that the same network can be used for the identification of the whole tumor, the enhancing tumor and the tumor core with great accuracy-0.908%, 0.784%, 0.844 respectively, while the method proposed in this paper is specialized on the detection of the whole tumor. For an extensive and complete review of deep learning techniques for GBM imaging we suggest Reference [82].…”
Section: Discussionmentioning
confidence: 99%
“…In [153], the cascaded network was proposed, which initially segmented the whole tumor followed by tumor core, and enhancing tumor segmentation refinement. In [79] authors had proposed cascaded UNet with three networks. The network processed downsampled input and generated output was passed to the next network in the cascaded sequence.…”
Section: Cnn Methods Classification For Tumor Segmentationmentioning
confidence: 99%